SOM Prevalance and Risk Factors in First Year Students of Primary Schools in the Region of Elazığ Abdullahpaşa Training and Research Health Center - Çetinkaya, Tufan; Ozan, A. Tevfik (Fırat University, 2001)
Objective: Secretory Otitis Media (SOM affects comprehension abilities and language progresion in preschool and schooltime children. The aim of the present study was to demonstrate the connection between SOM prevalance and risk factors in 1st class students who in the region of Elazığ Abdullahpaşa Training and Research Health Center's first education schools. Material and method: There were 232 children in the 1st class of the primary schools in study region. The children with SOM constituted the study group whereas, children with no signs and symptoms of SOM were control group. The results were evaluated by assessing the risk factors, sex, socioleconomic situation and success of the children in the schools. Results: In our study, SOM prevalance was found 15,9% and the correlation between SOM and risk factors was also determined. It was determined that the children with SOM were less succesfull than normal population. Conclusion: To determine correlation between SOM and risk factors, to be done school scanning by specialist personnel effects the succes of therapy positively, and provides to have healty and succesfull genius.

Amaç: Sekretuar Otitis Media (SOM) okul öncesi ve okul çağındaki çocuklarda kavrama yetenekleri ve lisan gelişimini etkilemekle birlikte tedavi için yapılan harcamalarla ülke ekonomisine önemli miktarda bir yük getirmektedir. Çalışmamızda Elazığ Abdullahpaşa Eğitim ve Araştırma Sağlık Ocağı bölgesindeki ilköğretim okulları 1. sınıf öğrencilerinde SOM prevalansının ve risk faktörleri ile olan ilişkisinin ortaya konulması amaçlanmıştır. Gereç ve yöntem: Çalışma bölgesindeki ilköğretim okullarının 1. sınıflarında okuyan 232 çocuktan otolojik muayene sonrası SOM tespit edilenler çalışma grubunu, tespit edilmeyenler kontrol grubunu oluşturdu. Sonuçlar risk faktörleri, cinsiyet, sosyoekonomik durum ve okul başarısı göz önünde bulundurularak değerlendirildi. Bulgular: Çalışmamızda SOM prevalansı %15.9 olarak bulundu. SOM'un risk faktörleri ile olan ilişkisi belirlendi. SOM görülen çocukların normal populasyona göre okuldaki başarılarının düşük olduğu tespit edildi. Sonuç: SOM'un risk faktörleri ile olan ilişkisinin ortaya konulması, okul taramalarının uzman personelce yapılması tedavide başarı oranını olumlu yönde etkileyerek geleceğe sağlıklı ve başarılı nesiller yetiştirilmesini sağlayacaktır.
ELAZIĞ ABDULLAHPAŞA EĞİTİM VE ARAŞTIRMA SAĞLIK OCAĞI BÖLGESİNDEKİ İLKÖĞRETİM OKULLARI 1. SINIF ÖĞRENCİLERİNDE SOM PREVALANSI VE RİSK FAKTÖRLERİ